Bhāshāra mūlyāẏana - Ray, Punya Sloka (Kalakātā : Śaṅkara Prakāśana, 1976)
Articles on the construction and usages of language; with special reference to Bengali.
Also issued online.
In Bengali; includes phrases in English.
committed to retain
Keywords: Bengali language -- Usage; Bengali language -- Usage